The Determinants of Renewable Electricity Share in a Just Energy Transition: An ARDL Analysis of Economic, Emissions, and Energy Access Factors - Kanayo, Ogujiuba; Lethabo, Maponya (International Journal of Economics and Financial Issues, 2025)
The urgent need to shift to sustainable energy systems is critical for South Africa, where deep-rooted fossil fuel reliance coincides with significant socio-economic and environmental issues. Although the potential of renewable electricity for promoting decarbonization and inclusive development is acknowledged, the macroeconomic and institutional factors influencing its share in a just energy transition are still inadequately examined. This study examines the changing interactions among economic growth, carbon emissions, and energy access in shaping South Africa’s share of renewable electricity. Utilizing the Autoregressive Distributed Lag (ARDL) bounds testing method, the analysis reflects both short-term dynamics and long-term equilibrium relations among the chosen variables. The findings indicate a statistically significant positive relationship between carbon dioxide emissions and the proportion of renewable electricity, implying that environmental decline could stimulate investments in renewables through regulatory or financial motivators. On the contrary, both GDP per capita and access to electricity show negative relationships with the share of renewable electricity, emphasizing the ongoing reliance on fossil-fuel-driven growth and centralized energy access approaches. These results reveal systemic compromises among economic growth, increased energy accessibility, and environmental sustainability. Policy suggestions highlight the incorporation of decentralized renewables into electrification initiatives, alignment of industrial strategies with green growth objectives, and enhanced institutional collaboration to promote South Africa's equitable transition agenda. Future studies ought to broaden to comparative panel analyses throughout the Southern African area and include distributive justice metrics to guide fair energy policy development.